Implementasi Komunikasi Online antara Dokter dan Pasien melalui Telemedicine di Masa Pandemi Covid-19 - Pascaningrum Sunaryo, Silvia (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Hospitals and other healthcare institutions are required to offer patient-centred, integrated, safe, effective and timely healthcare services. .In the Covid-19 pandemic situation, the use of telemedicine is very important to ensure medical personnel can provide health services to the public without transmitting the Covid-19 virus. The purpose of this study is to determine the success of implementing online communication between doctors and patients through telemedicine during the Covid-19 pandemic. This type of research is literature review. This research uses sources from well-known journals and Googlescholar. The data analysis technique is by using data analysis techniques with discourse analysis. The results of the study show that communication via telemedicine during the Covid-19 period between patients and doctors has had a significant positive impact. Even though there are indeed several studies which state that telemedicine is not effective for diagnosing patients. Telemedicine is successfully helping patients perform Hospitals and other healthcare institutions are required to offer patient-centered, integrated, safe, effective, and timely healthcare services. Technology facilitates access to health, but good quality health services remain a top priority. In the Covid-19 pandemic situation, the use of telemedicine is very important to ensure that medical personnel can provide health services to the public without transmitting the Covid-19 virus. The use of telemedicine is very important to ensure that medical personnel can provide health services. Online health services are an alternative that is needed by the community.